Parkinson’s disease gait rehabilitation at scale: Insights on personalised smartphone-based music cueing - Conor Wall; Amber Sacre; Peter McMeekin; Richard Walker; Victoria Hetherington; Yunus Celik; Rodrigo Vitorio; Rosie Morris; Alan Godfrey (PLoS ONE, 2026)
This study investigates the perceptions of people with Parkinson’s Disease (PwPD) regarding the use of a smartphone-based music cueing application (app). We present CuePD , an app for PwPD to use on their own smartphone for prescribed daily gait retraining/rehabilitation to reduce falls. Patient and public involvement and engagement (PPIE) is fundamental to ensuring the development of CuePD as a user-centred platform that effectively incorporates the lived experiences, insights, and needs of PwPD into its design and implementation. A qualitative vignette-based focus group was conducted, comprising seven PwPD and one caregiver, to gather insights on the acceptability and perceived utility of CuePD . Through open-ended questioning, participants’ existing routines were explored, including obstacles in sustaining an active lifestyle, and whether CuePD could routinely support gait rehabilitation in the home and beyond. The transcript was analysed using a reflexive thematic approach, of which four themes were constructed: (i) exercise preferences and routines, (ii) motivation and engagement, (iii) daily challenges and support, and (iv) app features and usability. Participants expressed a general openness to incorporating CuePD into their routines, emphasising the importance of personalised, engaging, and supportive solutions to enhance motivation and adherence to exercise. However, concerns were raised regarding the usability of CuePD features and the desire for more feature customisation to meet PD-specific needs and preferences. Overall findings suggest the potential of CuePD in supporting personalised and accessible gait rehabilitation through music cueing. CuePD may encourage active participation in disease management, better communication with healthcare professionals, and improve the overall quality of life for PwPD. More generally, this study highlights a significant interest among PwPD in using innovative technologies for rehabilitation, pointing towards the need for further development and user-centred design in PD-based mobile health (mHealth) solutions.